A Comparative Study on Traditional Face-to-Face Assessments Versus Online Assessments - Loo Ee Ng; Chin Kuo Ren; Mohd Khairil Abdul Karim; Nooradelana Mohd Ruslim (ALTSA Publisher, 2021)
This research aims to find an answer to the ongoing debate about the effectiveness of online learning. In this study, students’ academic performance based on continuous assessments and examination results were the indicator of effectiveness in learning. Descriptive analysis was used to compare students’ academic performance in grade point average (GPA) calculation in traditional face-to-face assessments and online assessments. Researchers also interested to find out about the attitudes of students and lecturers towards assessments in these two modes. Hence, a set of questionnaire is prepared with questions related to user’s experience, perceptions and preference while comparing traditional face-to-face assessments and online assessments. Findings from this study showed better academic performance in grade point average calculation where online assessments were conducted. Students’ responses in the questionnaire indicated online assessments are easier to do and easier to score; online assessments encourage independent learning and majority prefer online assessments. However, lecturers’ responses in the questionnaire indicated otherwise; higher percentages of lecturers preferred traditional face-to-face assessments to online assessments. From lecturers’ point of view, the traditional face-to-face assessments are fairer and less opportunity for cheating, hence, they are more confident in students’ answers and the results would reflect more accurately students’ actual learning achieved. This study concluded that online platform is an effective tool of learning and is well received and preferred among students.